2019
DOI: 10.3389/fpsyt.2018.00751
|View full text |Cite|
|
Sign up to set email alerts
|

Characterizing the Interplay Between Autism Spectrum Disorder and Comorbid Medical Conditions: An Integrative Review

Abstract: Co-occurring medical disorders and associated physiological abnormalities in individuals with autism spectrum disorder (ASD) may provide insight into causal pathways or underlying biological mechanisms. Here, we review medical conditions that have been repeatedly highlighted as sharing the strongest associations with ASD—epilepsy, sleep, as well as gastrointestinal and immune functioning. We describe within each condition their prevalence, associations with behavior, and evidence for successful treatment. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
98
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(104 citation statements)
references
References 246 publications
(277 reference statements)
4
98
0
2
Order By: Relevance
“…The diagnostic criterion for autism spectrum disorder (ASD) is based upon behavioral symptoms that include a combination of social‐communication deficits occurring along with repetitive and restrictive behaviors and interests [American Psychiatric Association, ]. Despite the fact that ASD is defined by behavior, it is now recognized as being associated with a large number of co‐occurring medical conditions (COCs) beyond the core behavioral symptoms [Tye, Runicles, Whitehouse, & Alvares, ]. A recent study from the Autism and Developmental Disabilities Monitoring Network found over 95% of children with ASD to be affected by at least one COC [Soke, Maenner, Christensen, Kurzius‐Spencer, & Schieve, ].…”
Section: Introductionmentioning
confidence: 99%
“…The diagnostic criterion for autism spectrum disorder (ASD) is based upon behavioral symptoms that include a combination of social‐communication deficits occurring along with repetitive and restrictive behaviors and interests [American Psychiatric Association, ]. Despite the fact that ASD is defined by behavior, it is now recognized as being associated with a large number of co‐occurring medical conditions (COCs) beyond the core behavioral symptoms [Tye, Runicles, Whitehouse, & Alvares, ]. A recent study from the Autism and Developmental Disabilities Monitoring Network found over 95% of children with ASD to be affected by at least one COC [Soke, Maenner, Christensen, Kurzius‐Spencer, & Schieve, ].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely known that ASD have many associated disorders [ 14 ]. Moreover, our results revealed that several disorders such as digestive disorders, intellectual disability and epilepsy are present in the ASD patients of our study.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that, three-quarters of children with ASD may also have another medical, psychiatric, or neurological disorder, including attention-deficit hyperactivity disorder, anxiety, bipolar disorder, inflammatory bowel disease, epilepsy, fragile X syndrome, gender dysphoria, intellectual disability, neuroinflammation and immune disorders, non-verbal learning disorder, obsessive-compulsive disorder, schizophrenia, sensory problems, sleep disorders, tuberous sclerosis, Tourette syndrome and tic disorders (Sharma et al 2018;Tye et al 2019). In our study, half of the children with autism have intestinal problems, and almost all the children with this problem have also developed fungal infections.…”
Section: Resultsmentioning
confidence: 99%